Cold‐born killers: exploiting temperature–size rule enhances predation capacity of a predatory mite. Issue 5 (27th December 2019) - Vangansbeke, Dominiek; Duarte, Marcus VA; Gobin, Bruno; Tirry, Luc; Wäckers, Felix; De Clercq, Patrick
Abstract: BACKGROUND: The temperature–size rule is a well‐known example of phenotypic plasticity in ectothermic organisms. When exposed to colder temperatures, ectotherms develop more slowly, but mature at larger body sizes and vice versa at higher temperatures. We investigated whether a phytoseiid predatory mite can obtain a larger body size by rearing it at a low temperature and how the increased body size affected predatory performance on its natural prey. Therefore, we allowed the predatory mite Amblydromalus limonicus (Garman & McGregor) (Acari: Phytoseiidae) to develop at either 15 or 25 °C. RESULTS: A. limonicus reared at 15 °C had a 6% larger body size than those reared at 25 °C. Larger predators showed higher predation rates on first instars of the western flower thrips, Frankliniella occidentalis Pergande (Thysanoptera: Thripidae), with 9.6 instars/female/day and 8.5 instars/female/day, for larger and standard‐sized females, respectively. After three generations reared at 15 °C, body size did not increase any further. When reared for five generations at 15 °C, larger A. limonicus females demonstrated a better ability to subdue second‐instar F. occidentalis . CONCLUSION: Low juvenile rearing temperatures may result in phytoseiid predators with a predator/prey size benefit that could improve their biological control function. © 2019 Society of Chemical Industry Abstract : Cold rearing temperature resulted in higher predation capacities on first instar thrips.